"Líneas de piedra" en suelos del noreste argentino. Origen e implicancias. - Moretti, Lucas Martin; Morras, Hector (Asociación Argentina de la Ciencia del Suelo (AACS), 2025)
Los suelos rojos del noreste argentino (Ultisoles, Oxisoles y Alfisoles) presentan frecuentemente capas “pedregosas”, usualmente conocidas como “líneas de piedra” en la literatura, y cuyo origen ha sido objeto de diversas interpretaciones. Para el caso de la provincia de Misiones, nuestros resultados nos han permitido diferenciar dos tipos principales de niveles pedregosos formados in situ como consecuencia de la meteorización del basalto, y que de acuerdo con su génesis y composición denominamos “horizontes de nódulos ferruginosos” y “horizontes silíceos”, ambos frecuentemente asociados a “horizontes estructurados en bloques”. En el primer caso los nódulos se formarían en las coladas de basalto masivo a partir de la caolinización de las plagioclasas, alteración los minerales ferromagnesianos y acumulación de un plasma ferruginoso, mientras qué en el segundo, consistirían en venas relícticas de cuarzo heredadas del basalto vesicular y amigdaloide. Los horizontes estructurados se formarían a partir del desarrollo de una matriz arcillosa entre los nódulos a medida que éstos se van individualizando, o a partir de un “efecto de protección” ante el frente de meteorización que ejercerían los horizontes silíceos sobre los materiales de textura fina, subyacentes en el saprolito. Por otro lado, si bien no se cuenta con información suficiente acerca de las implicancias de estos horizontes en los suelos rojos de Misiones, se pueden realizar algunas estimaciones. En cuanto al desarrollo vegetal los horizontes nodulares constituirían un impedimento relativamente menor respecto de los silíceos para el crecimiento radicular. Además, en los perfiles suelen encontrarse varios horizontes silíceos superpuestos lo que incrementaría la restricción para la penetración de raíces. Respecto a la dinámica del agua debe tenerse en cuenta la profundidad, morfología, cantidad, espesor y composición de los horizontes pedregosos, siendo los nodulares más permeables que los silíceos. Vinculado con la influencia de estos horizontes en los flujos hídricos debe considerarse el eventual rol de los horizontes pedregosos en los procesos erosivos. En este sentido, dado la disminución de la permeabilidad que representan en particular los horizontes silíceos, estos podrían dar lugar a la circulación lateral hipodérmica del agua, a la generación de escurrimiento superficial, y eventualmente a la erosión del suelo. Si bien hasta el presente las “líneas de piedra” han sido localmente poco consideradas, el presente trabajo brinda una importante base de conocimiento acerca de su génesis y posibles implicancias en los suelos del noreste argentino. The dense layers of natural origin most known in Argentina, according to the geological, geomorphological and edaphic predominant characteristics in the country, are the petrocalcic horizons and the fragipans. However, in the ferruginous and ferrallitic soils of the subtropical environment in the northeast of the country, “stony layers” frequently appear, whose presence and origin have not been sufficiently studied until now. These levels of accumulation of thick fragments -often of gravel size- which are frequent in tropical and subtropical soils, have been called “stone lines” and their genesis is a controversial matter that has deserved numerous interpretations in the international literature. In this regard, the different hypotheses about the material composing this type of profile can be grouped as of authochtonous or allochtonous origin, although others more complex scenarios have been also postulated. The earliest studies that refer to an allocthonist explanation comprise two-stage processes, made up by a first stage of deflation and surface exposure of pebbles, and a second one of burial of pebbles by sedimentation. On the other hand, the authochtonist models basically refer to processes of differential weathering and to the remobilization of materials within the profile, this last as a consequence of gravity or promoted by the soil fauna. Moreover, several authors have also presented general explanations that involve the simultaneous effect of different dynamic processes which are driven by gravity, water and biotic agents. In relation to these interpretations, diverse horizon nomenclatures -either the conventional ABC system or other symbology- have also been proposed for the morphological soil description. It is to be noted that most of the soil classification systems consider the stone line as a discordance. The red soils with stony horizons of northeastern Argentina (Provinces of Misiones and Corrientes), classified as Ultisols, Alfisols and Oxisols, has been traditionally considered to be the result of in situ weathering of the basaltic rock. However, in the 1990s it was also postulated that superficial material in which the red soils have developed is an eolian sediment (“Tropical loess”) of upper Pleistocene age, deflated from the alluvial plains of the Paraná and the Uruguay rivers. The main arguments supported by the authors were the presence of a “stone line” -also assumed as sedimentary and constituted by siliceous platy-gravels- together with a structured level below it, which was interpreted as a paleosol. Conversely, on the basis of field observations of numerous profiles and detailed studies in several of them with a wide diversity of analytical techniques, we conclude that the parent material of the soils as well as the “stone lines” and the blocky structured horizons associated, are the result of in situ weathering of the basaltic rock. Therefore, we denominate these stony layers as “horizons”. Moreover, two types of those “stony horizons” were identified in Misiones in relation to their origin, composition and morphology. The first is a “nodular ferruginous horizon”, more typical in the southern part of Misiones, composed mainly by hematitic and goethitic nodules of gravel size, and generally appearing at the soil-saprolite interface. Although their genesis need to be studied in detail, the individualization of spheroidal fragments could be linked to the processes of “spheroidal weathering” -specifically mentioned for the massive basalts of Misiones- which would include a caolinization of plagioclases, alteration of ferromagnesian minerals and a relative accumulation of a ferruginous plasma. The second one is a “siliceous horizon” of quarzitic nature, characterizing profiles in central Misiones. These silica concentrations are clearly in situ relicts of former hydrothermal quartz veins in the vesicular and amygdaloidal basalt flows. Concerning the “blocky structured horizons” below the stony horizons, field work and analytical data let conclude that they are not buried paleosols and two processes may be esponsible for the formation of these structured layers: 1) Argilliplasmation together with ferrugination and development of iron nodules as a consequence of weathering of massive basalt flows; in this case, the clayey matrix surrounding the nodules result in polyhedral aggregates differing from the microstructure in the solum which is mostly characterized by rounded peds. 2) A “protective” effect exerted by the siliceous horizons against the weathering front, thus allowing the development and conservation of structural blocky units from the fine textured materials in the saprolite underlying. On the other hand, the implications of the “stone lines” on soil physical properties and in the landscape dynamics through its influence on the hydrological processes, have been much less considered. Its impact in plants growing and in soil quality from an agronomic point of view will be varied and will depend, among other factors, on the abundance, size, composition, degree of consolidation and depth to which the thick fragments are found in the profile. Respect to the role of nodular and siliceous horizons as impedance levels in the red soils of Misiones, it has been observed that the roots of tree plants or natural grasses abruptly change direction and develop horizontally in contact with the two types of stony horizons, while the proportion of roots decreases abruptly below them. In addition, according to their morphology and composition, it can be assumed that nodular horizons represent a relatively minor impediment compared to siliceous horizons. Regarding to the water dynamics, the influence of four factors should be considered: 1) the depth of the stony horizon within the soil profile, which will determine both the percolation and the amount of water stored; 2) the morphology of these horizons in terms of lateral development and also thickness; 3) the type of horizon, because the nodular one are more permeable, while the siliceous one would be more restrictive for the vertical flow of water; and 4) the existence of several parallel stony horizons in the same profile, thus introducing a great complexity on the retention and flow of water in the soil and consequently in their measuring. On the other hand, the presence of nodular horizons in the red soils of Misiones can be presumed to act as rock fragments, thus contributing to percolation and reducing the risk of erosion. A different situation would occur with the siliceous horizons due to their relative impermeability, although this will depend on its continuity, morphology and depth within the soil profile. Thus, although until recently the stony horizons in the northeastern part of the Argentina have been ignored in pedological, geomorphological and agronomic research, the recent results and interpretations about their genesis and implications already offer a new conceptual basement and suggest the interest of further deepening their study.